Home Security And Access System Prototype Using Fingerprint - Muh. Fahrurrozi; Lalu Puji Indra Kharisma (IJISTECH (International Journal of Information System and Technology), 2021)
A sense of security and easy access in managing the house is a must that every home must-have. With advances in technology, it makes it easy for us to manage and maintain the security of our homes, one of which is by utilizing an embedded system in home management using fingerprints. Fingerprints are used as the main key to access the house to provide a sense of security, convenience in managing the house, and minimizing cases of theft that occur in houses that still use conventional keys. based on trials carried out the use of fingerprints is easier to use than using an ordinary key with a success rate in the test, namely 100% in a clean and not wet state, 40% in wet fingerprints, and 0% in dirty fingerprints or dusty.